2021
DOI: 10.3389/fonc.2021.759811
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Haar Feature-Based Endoscopic Ultrasound Probe Tracking for Implanting Hydrogel Spacer in Radiation Therapy for Pancreatic Cancer

Abstract: PurposeWe proposed a Haar feature-based method for tracking endoscopic ultrasound (EUS) probe in diagnostic computed tomography (CT) and Magnetic Resonance Imaging (MRI) scans for guiding hydrogel injection without external tracking hardware. This study aimed to assess the feasibility of implementing our method with phantom and patient images.Materials and MethodsOur methods included the pre-simulation section and Haar features extraction steps. Firstly, the simulated EUS set was generated based on anatomic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…However, the main challenge is the registration of 2D ultrasound images to the CT and measuring the amount of separation, which is the aim of our current and future studies. [46][47][48] We are aware that our study has a few limitations. First, due to the novelty of the duodenal spacer, the number of cases is very limited and has not been widely used in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the main challenge is the registration of 2D ultrasound images to the CT and measuring the amount of separation, which is the aim of our current and future studies. [46][47][48] We are aware that our study has a few limitations. First, due to the novelty of the duodenal spacer, the number of cases is very limited and has not been widely used in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…We found that spacer benefit for a high-dose volume is highly dependent on the patient’s anatomy and spacer location. Future work focuses on (1) improving the software and reliability of the model by incorporating a larger patient cohort, (2) adding more features to the DSS such as prediction of toxicity and cost-effectiveness, and (3) proposing a new workflow featuring preoperative simulation and intraoperative guidance to personalize and optimize the duodenal spacer procedure based on our studies on wavelet-based image guidance ( 25 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…As with other approaches to holding the lesion away from the surrounding organs, there is the surgical method to insert a tool called a “spacer.” The materials of the spacer vary depending on the targets. Blood patch, human collagen, acellular human dermis ( Ismael et al, 2016 , Dalwadi et al, 2019 ), hyaluronic acid, and polyethylene-glycol hydrogel have been used, mainly via injection for prostate cancer ( Tang et al, 2018 , Ismael et al, 2016 , Feng et al, 2021 ). Since the first report of the clinical use of spacers in 1984 ( Dürig et al, 1984 ), several placement methods and materials of spacers have been reported in head and neck cancer ( Shibuya, 2009 ) and abdominal pelvic tumors ( Sezeur et al, 1999 ), liver ( Ismael et al, 2016 ), retroperitoneal tumor, and pancreatic cancer ( Feng et al, 2021 ), and researched very intensively in prostate cancer ( Tang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Blood patch, human collagen, acellular human dermis ( Ismael et al, 2016 , Dalwadi et al, 2019 ), hyaluronic acid, and polyethylene-glycol hydrogel have been used, mainly via injection for prostate cancer ( Tang et al, 2018 , Ismael et al, 2016 , Feng et al, 2021 ). Since the first report of the clinical use of spacers in 1984 ( Dürig et al, 1984 ), several placement methods and materials of spacers have been reported in head and neck cancer ( Shibuya, 2009 ) and abdominal pelvic tumors ( Sezeur et al, 1999 ), liver ( Ismael et al, 2016 ), retroperitoneal tumor, and pancreatic cancer ( Feng et al, 2021 ), and researched very intensively in prostate cancer ( Tang et al, 2018 ). Recently, a meta -analysis confirmed the benefit of percutaneous SpaceOAR TM Hydrogel injection for prostate cancer temporarily distances the rectum from the prostate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation